Anticytotoxic T-Lymphocyte Antigen-4 Induced Autoimmune Hypophysitis: A Case Report and Literature Review. (28th January 2015) - Majchel, Deborah; Korytkowski, Mary T.
Abstract : Objective . We describe a case of autoimmune hypophysitis induced by the anticytotoxic T-lymphocyte antigen-4 (CTLA-4) agent, ipilimumab. Methods . Case presentation and review of the literature. Results . Autoimmune hypophysitis, a previously described rare disorder, is being recognized more frequently as a side effect of novel immunomodulatory agents used in the treatment of malignancies such as melanoma. CTLA-4 agents are associated with immune-related adverse effects (irAE) which occur as a result of activation (or lack of inactivation) of the immune response. This impacts not only malignant cells but also different host organ-systems. Autoimmune hypophysitis is one of several endocrinopathies associated with these agents. Conclusion . It is important that endocrinologists become familiar with the endocrinopathies, such as autoimmune hypophysitis, associated with new immunomodulator agents which are being used with increasing frequency to treat a variety of malignancies.